Theory "Tirі bilim" A. Baytursynuly – the basis for the formation of a worldview about the language (Eurasian Journal of Philology Science and Education, 2023)
The article discusses the possibilities of implementation and pedagogical conditions for using the theory of A. Baitursynuly "Living knowledge" in the process of modern education. The priorities of the teachings of the founder of the methodology of teaching the Kazakh language are proved.The formation of students' worldview about the language begins with their awareness of the importance of education for his life. Because a person can use only that knowledge when he understands its meaning and meaning, when he masters the methods of using it. Therefore, it is important to combine tradition and innovation in the process of language learning. This is done by applying the category "manis bilim", "adіs bilim", "paydaly bilim" in the theory of "Living Knowledge" of the scientist.The article explains the ways of organizing the study of nouns according to the theory of Akymet Baitursynuly "Living Knowledge", the methods of forming students' worldview about their native language and functional literacy in general are proposed. The conceptual foundations of the category "paidal bilim" are argued. For this, the method of comparing education quality indicators was used.